2003
DOI: 10.1046/j.1523-1747.2003.12127.x
|View full text |Cite
|
Sign up to set email alerts
|

Six Novel P Gene Mutations and Oculocutaneous Albinism Type 2 Frequency in Japanese Albino Patients

Abstract: Type 2 oculocutaneous albinism (OCA2) is an autosomal recessive disorder that results from mutations in the P gene that codes one of the melanosomal proteins, the function of which remains unknown. In this paper, we report the frequency of OCA2, 8%, among the Japanese albino population, six novel mutations containing four missense substitutions (P198L, P211L, R10W, M398I), and two splice site mutations (IVS15+1 G>A, IVS24-1 G>C). One of them, R10W, was within the putative signal peptide at the N-terminal of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 22 publications
2
27
0
Order By: Relevance
“…Direct sequencing of aberrant bands found with the SSCP screening method finally detected compound heterozygous P gene mutations, M394I (ATG→ATA) and A481T (GCC→ACC; fig. 2), which had already been reported in previous studies [4, 5]. …”
Section: Case Reportsupporting
confidence: 83%
See 2 more Smart Citations
“…Direct sequencing of aberrant bands found with the SSCP screening method finally detected compound heterozygous P gene mutations, M394I (ATG→ATA) and A481T (GCC→ACC; fig. 2), which had already been reported in previous studies [4, 5]. …”
Section: Case Reportsupporting
confidence: 83%
“…More than 50 different mutations of the P gene have been reported. The M394I mutant allele, which was found in the present case, has been found in Japanese patients of OCA2 with no or very low functional activity in melanogenesis [4]. On the other hand, the A481T mutant allele has been described to have approximately 70% functional activity in melanogenesis compared with that of the normal allele based on the results of a transfection experiment of p null mouse melanocytes with the A481T mutant P cDNA [9].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In addition, to date, several potential functions, such as a membrane transporter of a substrate [26] and a sorter of tyrosinase to the melanosome [27], have been proposed for the P protein. Mutations in the P gene are associated with oculocutaneous albinism type II (OCA2), which is the most common type of human albinism [28][29][30][31], and phenotypic variations in human iris color [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…A c.G1559A (Ala481Thr; unregistered in Entrez SNP) mutation in exon 14 was first discovered as a compound heterozygote in a European-American patient with apparent autosomal recessive ocular albinism, and its frequency was estimated to be 0.01 in the testing of 50 unrelated normal Caucasian subjects (Lee et al 1994). Thereafter, this mutant allele, OCA2*481Thr, has sporadically been observed in Japanese OCA2 patients (Saitoh et al 2000;Kato et al 2003;Suzuki et al 2003a;Kawai et al 2005;Ito et al 2006) and a German patient with congenital cataract and macular hypoplasia (Graw et al 2006). A transfection study showed that OCA2*481Thr had approximately 70% function of the wild type allele in melanogenesis and confirmed it was a relatively mild OCA2 allele (Sviderskaya et al 1997).…”
Section: Introductionmentioning
confidence: 99%